ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU DAN AUDIT DELAY PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2007-2011) - Karina Mutiara Dewi; Sugeng Pamudji (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to analyze the factors that affect timeliness and audit delay of financial reports to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are profitability, solvability, company size, the size of a public accounting firm and auditor's opinion as the independent variables while the timeliness and audit delay as the dependent variables. The sample consists of 335 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam consistently in the period 2007-2011. The data that was used in this research was secondary data and selected by using purposive sampling method. The analysis tool used is multiple regression analysis to measure audit delay, logistic regression to measure timeliness and spearman correlation to measure the relationship between audit delay and timeliness. The partial hypothesis test results show that solvability, auditor’s opinion, and the size of the public accounting firm have significant effect on audit delay, and size of firm and auditor’s opinion have significant effect on timeliness. The correlation result show that audit delay have significant effect on timeliness.